2004
DOI: 10.1111/j.1365-2966.2004.07951.x
|View full text |Cite
|
Sign up to set email alerts
|

On the source of the late-time infrared luminosity of SN 1998S and other Type II supernovae

Abstract: We present late‐time near‐infrared (NIR) and optical observations of the Type IIn SN 1998S. The NIR photometry spans 333–1242 d after explosion, while the NIR and optical spectra cover 333–1191 and 305–1093 d, respectively. The NIR photometry extends to the M′ band (4.7 μm), making SN 1998S only the second ever supernova for which such a long IR wavelength has been detected. The shape and evolution of the Hα and He i 1.083‐μm line profiles indicate a powerful interaction with a progenitor wind, as well as prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
209
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(224 citation statements)
references
References 105 publications
(255 reference statements)
15
209
0
Order By: Relevance
“…Dust formation in the ejecta is thought to give rise to asymmetric and blueshifted H line profiles in some SNe II, but this occurs at later times when the temperature of the ejecta has dropped below a few thousand K, normally more than 200 days postexplosion (e.g., Elmhamdi et al 2003;Wooden et al 1993;Pozzo et al 2004;Sugerman et al 2006). Our spectra show no pronounced asymmetric profiles in the hydrogen emission lines through day 463 (Fig.…”
Section: Dual-axis Modelmentioning
confidence: 81%
“…Dust formation in the ejecta is thought to give rise to asymmetric and blueshifted H line profiles in some SNe II, but this occurs at later times when the temperature of the ejecta has dropped below a few thousand K, normally more than 200 days postexplosion (e.g., Elmhamdi et al 2003;Wooden et al 1993;Pozzo et al 2004;Sugerman et al 2006). Our spectra show no pronounced asymmetric profiles in the hydrogen emission lines through day 463 (Fig.…”
Section: Dual-axis Modelmentioning
confidence: 81%
“…In particular, Smith et al (2008b) demonstrated that the relative strength of the systematic blueshift seen in He i lines at different wavelengths was consistent with the wavelength-dependent extinction one expects from small dust grains. This provided the first solid example of dust formed in the dense post-shock cooling zone of an SN dominated by CSM interaction, although it had been noted earlier as a possibility in the case of the SN IIn 1998S (Pozzo et al 2004). Subsequently, Matilla et al (2008) presented mid-IR data for SN 2006jc and additional spectra, yielding similar results.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence for post-shock dust formation has also been reported in a few examples of Type IIn SNe that are not expected to have C-rich ejecta. These include SN 1998S (Pozzo et al 2004), SN 2005ip (Smith et al 2009Fox et al 2009), and SN 2006tf (Smith et al 2008a). More recently, some of the SNe IIn studied by Fox et al (2011) also show possible evidence for dust formation, although these authors conclude based on the observed dust temperature that the bulk of the IR excess was probably due to an IR echo in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…As it was found in some CC SNe (e.g. SN 1998S, Pozzo et al 2004;SN 2005ip, Smith et al 2009and Fox et al 2009;SN 2006jc, Smith et al 2008aSN 2006tf, Smith et al 2008bSN 2007od, Andrews et al 2010, dust grains may condense in a cool dense shell (CDS) that is generated between the forward and reverse shock waves during the interaction of the SN ejecta and the preexisting circumstellar medium (CSM). The CDS may affect both the light curves and the spectral line profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is the thermal radiation of pre-existing dust in the CSM that is re-heated by the SN as an IR-echo (Bode & Evans 1980;Dwek 1983Dwek , 1985Sugerman 2003), which can be observed as an infrared excess (e.g. SN 1998S, Gerardy et al 2002Pozzo et al 2004;SN 2002hh, Barlow et al 2005Meikle et al 2006;SN 2006jc, Mattila et al 2008SN 2004et, Kotak et al 2009SN 2008S, Botticella et al 2009). These results seem to support the hypothesis that pre-explosion mass-loss processes of progenitor stars could play a more important role in dust formation than the explosions of CC SNe (see also Prieto et al 2008;and Wesson et al 2010).…”
Section: Introductionmentioning
confidence: 99%